About Higher Efficiency Pertaining to Usage of Power Transformers at Industrial Enterprises - V. N. Radkevich; A. L. Trushnicov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2008)
Problems pertaining to higher efficiency of power transformer usage at industrial enterprises and application of automatic control systems at transformer sub-stations are considered in the paper. The paper contains a simplified function scheme of such system.